TRANSFORMING CONSUMER BEHAVIOR IN THE DIGITAL AGE: A REVIEW OF THE INTEGRATIVE LITERATURE IN THE PERSPECTIVE OF ISLAMIC CONSUMPTION ETHICS - Siti Harizah; Isnaliya Isnaliya; Zakiatus Zahroh (IJED: International Journal of Economy Development Research, 2026)
Consumer behavior has shifted from a relatively linear purchasing process toward a dynamic, data-intensive, and socially mediated decision journey. Classical explanations that emphasize personal, psychological, social, and cultural determinants remain relevant, but they are insufficient to explain the growing role of social media, electronic word of mouth, influencers, algorithms, platform design, and personalized digital marketing. This article aims to synthesize these developments and to formulate an integrative conceptual framework that connects contemporary consumer decision processes with Islamic consumption ethics. The study employs an integrative literature review by combining foundational consumer behavior literature with recent peer-reviewed studies on digital marketing, social media, ethical consumption, religiosity, and Muslim consumer decision making. The literature is analyzed thematically across four dimensions: consumer decision processes, internal and external determinants, digital marketing stimuli, and Islamic ethical filters. The synthesis shows that digitalization does not eliminate classical determinants; instead, it amplifies, accelerates, and reorganizes their effects throughout the consumer journey. From an Islamic perspective, values such as moderation, avoidance of extravagance, honesty, fairness, halal awareness, and benefit orientation may function as evaluative filters that shape how consumers interpret digital stimuli and make purchase decisions. The article contributes by positioning Islamic ethics not merely as an additional normative variable, but as a cross-stage evaluative mechanism within the digital consumer journey. The proposed framework offers theoretical propositions and practical implications for responsible digital marketing and future empirical testing.